Plasma α-Glutathione S-Transferase Evaluation in Patients with Acute and Chronic Liver Injury - Jolanta Czuczejko; Celestyna Mila-Kierzenkowska; Karolina Szewczyk-Golec (Canadian Journal of Gastroenterology and Hepatology)
High concentration of alpha-glutathione S-transferase (α-GST) in the liver and its short half-life make this enzyme clinically useful in assessing hepatocellular damage. We aimed to investigate the significance of α-GST evaluation in monitoring of liver injury in acute and chronic liver diseases. 20 healthy volunteers and 52 patients were included in the study. The patients were divided into three groups: group I (acute viral hepatitis B or C), group II (chronic hepatitis B or C), and group III (chronic liver disease or cirrhosis with different etiologies). The concentration of α-GST and the activities of alanine aminotransferase (ALT) and aspartate aminotransferase (AST) were measured in all examined groups. α-GST, ALT, and AST were statistically higher in all patient groups than in the control group. Statistically higher values of all assessed parameters were observed in group I compared with remaining patients. Statistically higher activities of ALT and AST are observed in group III compared with group II. Significant positive correlations were noted between α-GST and ALT/AST in groups I and III. The results indicate that the assay of α-GST in combination with the other conventional markers may be found as a confirmatory test for hepatocellular damage.